2007
DOI: 10.1149/1.2718402
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance and X-Ray Absorption Spectroscopic Studies of Lithium Insertion in Silver Vanadium Oxide Cathodes

Abstract: Structural studies have been carried out on Ag 2 V 4 O 11 ͑silver vanadium oxide, SVO͒ and Li x Ag 2 V 4 O 11 , lithiated SVO with x = 0.72, 2.13, and 5.59 using nuclear magnetic resonance ͑NMR͒ and X-ray absorption spectroscopy ͑XAS͒. Lithium-7 NMR indicates the formation of a solid electrolyte interphase layer on the x = 0.72 sample and lithium intercalation into both octahedral and tetrahedral sites in the SVO lattice, and that most but not all of the Ag ͑I͒ is reduced prior to initiation of V͑V͒ reduction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…(5, 6, 7, 8, 9, 10) Further, the discharge process of SVO in a lithium battery has been investigated by several methods including titration, x-ray powder diffraction and solid state NMR. (10, 11, 12, 13) The discharge process of SVO initiates with the competitive reduction of Ag + to Ag 0 and of V 5+ to V 4+ and then proceeds to some reduction of V 4+ to V 3+ . Notably, the reduction of silver ion was observed to form silver metal nanoparticles and nanowires within the cathode and contribute to a significant increase in cell conductivity on discharge.…”
Section: Introductionmentioning
confidence: 99%
“…(5, 6, 7, 8, 9, 10) Further, the discharge process of SVO in a lithium battery has been investigated by several methods including titration, x-ray powder diffraction and solid state NMR. (10, 11, 12, 13) The discharge process of SVO initiates with the competitive reduction of Ag + to Ag 0 and of V 5+ to V 4+ and then proceeds to some reduction of V 4+ to V 3+ . Notably, the reduction of silver ion was observed to form silver metal nanoparticles and nanowires within the cathode and contribute to a significant increase in cell conductivity on discharge.…”
Section: Introductionmentioning
confidence: 99%
“…As has been previously reported for silvervanadium bimetallic materials, some vanadium reduction takes place in parallel with the reduction of silver. 25,[31][32][33]52 Previous studies of discharged Ag 2 V 4 O 11 [25][26] indicate that vanadium 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12 oxidation states of V, IV, and III can co-exist once the material is discharged past 2 electron equivalents. For Ag 2 VO 2 PO 4 , a recent X-ray absorption spectroscopy study 31 has shown that the vanadium is present as a mixture of oxidation states IV and III when the material is discharged to 3 electron equivalents.…”
Section: Ex-situ Cathode Characterizationmentioning
confidence: 99%
“…[22][23] While the reduction process of the cathode in the Ag 2 V 4 O 11 battery has been studied through characterization of the cathode material at various stages of discharge, analysis of the anode surface has not been reported. [24][25][26] There are limited reports of negative electrodes analyses from cells including those containing manganese oxide cathodes. 27 Surface films containing manganese(II) were detected on graphite electrodes using electrolytes contaminated with manganese ions and were associated with a ~15 times increase in the lithium-ion transfer resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the crossing composition from where the silver reduction is initiated is complex to be accurately determined from XRD because of the nano-crystallinity of the metal withdrawn. It is noteworthy the low reduction potential of silver ion in comparison with 3.45 V for SVOF [18], 3.35 V for SMOF [24], 3.25 V for SVO [48][49][50] or nearby 3 V for a and b-AgVO 3 [51].…”
Section: Article In Pressmentioning
confidence: 99%